1996
DOI: 10.1159/000188949
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-Related Pruritus: A Double-Blind, Placebo-Controlled, Crossover Study of Capsaicin 0.025% Cream

Abstract: Pruritus is a significant symptom among patients receiving hemodialysis. However, its underlying mechanisms remain obscure. Substance P, a neuropeptide, has been implicated in the mediation of pain and some itch sensations. Local application of capsaicin depletes the peripheral neurons of substance P and may block the conduction of pain or pruritus. This study aims to assess the efficacy and safety of capsaicin 0.025% cream in the treatment of hemodialysis-related pruritus and to further explore the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 17 publications
2
64
0
5
Order By: Relevance
“…16,28 Additionally, as uremia progresses, peripheral nervous system becomes more affected, especially the sensory parts. 21 On the other hand, reports showing the efficacy of lidocaine, 29 capsaicin, [30][31][32] and gabapentin 33,34 in controlling UP are in favor of a relationship between neuropathy and pruritus in HD patients. Thus, we can only hypothesize that even in nondiabetic patients, disturbed glucose metabolism as demonstrated by higher HbA1c levels, at least by inducing permissive role for the development of neuropathy, may result in increased sensation of itching.…”
Section: Discussionmentioning
confidence: 99%
“…16,28 Additionally, as uremia progresses, peripheral nervous system becomes more affected, especially the sensory parts. 21 On the other hand, reports showing the efficacy of lidocaine, 29 capsaicin, [30][31][32] and gabapentin 33,34 in controlling UP are in favor of a relationship between neuropathy and pruritus in HD patients. Thus, we can only hypothesize that even in nondiabetic patients, disturbed glucose metabolism as demonstrated by higher HbA1c levels, at least by inducing permissive role for the development of neuropathy, may result in increased sensation of itching.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Tarng et al [40] reported that 19 HD patients with idiopathic, moderate (n = 5) to severe (n = 14) pruritus were examined in a double-blind, placebo-controlled, crossover study, and 17 of them completed the study. Topical capsaicin or placebo base cream was applied to localized areas of pruritus 4 times a day.…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Proteases are pruritogenic substances and protease receptors have been described in the distal end of C fibers. Stimulation of these release substance P. Capsaicin inhibits substance P and inturn itching [25,26]. CKD associated pruritus patients also have neuropathy which is relieved with gabapentin [27].…”
Section: Mast Cellsmentioning
confidence: 99%
“…Capsaicin desensitizes the nociceptive nerve endings depletes the substance P in peripheral neurons and blocks the pain of pruritus. Side effect like burning sensation sometimes may make the patient to stop using it [26,47]. Similarly pramoxine based anti-itch lotion which is also a local anesthetic agent has reduced pruritus significantly.…”
Section: Capsaicinmentioning
confidence: 99%